Development and Usability Evaluation of the "Si BINTANG" Audiovisual Web Application for Integrated Child Growth and Development Monitoring - Sofia, Norlaila; Hapisah; Noor Adha Aprilea; Rusmilawaty; Yuniarti; Zakiah (Jurnal Teknokes, 2025)
Indonesia’s child growth monitoring system, essential for national stunting prevention, still relies on paper-based tools such as the Child Health Card (KMS), which often face challenges of low parental engagement, fragmented data management, and limited health literacy. Existing digital applications primarily function as data logbooks, lacking interactive audiovisual content that can effectively support parents with diverse literacy levels and learning needs. This gap highlights the urgency for innovative health communication strategies that bridge conventional and digital media to enhance participatory learning and improve community-based child monitoring practices. This study developed and evaluated Si BINTANG (Interactive Barcode-Based Growth and Development Information System). This hybrid audiovisual web platform connects a printed child monitoring book with digital content through QR code technology. The application was designed using a user-centered and health communication approach to enhance parental understanding, motivation, and engagement in monitoring their child's growth and development. A preliminary usability evaluation involving experts and mothers of children under five indicated high system quality, usability, and user acceptance, demonstrating positive responses across functionality, accessibility, and user satisfaction. These results suggest that hybrid digital–print integration can enhance health education by making it more interactive, inclusive, and accessible for families, particularly in low-literacy or resource-limited settings. While the findings show encouraging potential, this study acknowledges several limitations, including the small and localized sample size. Future research will focus on large-scale implementation and impact assessment on parental knowledge, behavioral change, and child health outcomes. The Si BINTANG platform represents a promising direction for strengthening family-based stunting prevention through hybrid digital innovation, contributing to Indonesia’s ongoing digital health transformation and community empowerment agenda.